The Role of Self-Care for Parents in Recovery From Substance Use Disorders: An Integrative Review of Parental Self-Care. Issue 3 (July 2016) - Raynor, Phyllis; Pope, Charlene
Abstract: Background: Lack of stress modifiers, such as self-care behaviors (SCBs), can increase vulnerability to drug use for parents in recovery from substance use disorders (SUDs). Purpose: The purpose of this integrative review was to determine how the existing literature describes, conceptualizes, and measures SCB for parents in the general population for its application to parents with a history of SUD. Methods: Framed by Bandura's Social Cognitive Theory of Substance Abuse, four qualitative and five quantitative studies identify SCB, although only one study describes SCB of parents in recovery. Results: Few studies addressed parental SCB, and most of those studies focused on behaviors for new mothers with or without SUDs during the early child years. Conclusions: Exploring the role of SCB in relation to parental well-being for the general population is a needed area for further research, even more so for parents who are recovering from SUDs.